2016
DOI: 10.1016/j.jphs.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Gomisin N ameliorates lipopolysaccharide-induced depressive-like behaviors by attenuating inflammation in the hypothalamic paraventricular nucleus and central nucleus of the amygdala in mice

Abstract: Emotional impairments such as depressive symptoms often develop in patients with sustained and systemic immune activation. The objective of this study is to investigate the effect of gomisin N, a dibenzocyclooctadiene lignan isolated from the dried fruits of Schisandra chinensis (Turcz.) Baill., which exhibited inhibitory effects of the bacterial endotoxin lipopolysaccharide (LPS)-induced NO production in a screening assay, on inflammation-induced depressive symptoms. We examined the effects of gomisin N on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Actually, STAT3 is activated through the phosphorylation of tyrosine, which was not assessed in our research. Lipopolysaccharide, a bacterial endotoxin, can induce depressive-like behavior [59]. Hosoi et al [60] found that i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, STAT3 is activated through the phosphorylation of tyrosine, which was not assessed in our research. Lipopolysaccharide, a bacterial endotoxin, can induce depressive-like behavior [59]. Hosoi et al [60] found that i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Atractylodis Rhizoma Alba was reported to inhibit inducible NO synthase [22] and inflammatory cytokines through mitogen-activated protein kinase (MAPK) and nuclear factor κB (NF-κB) [23,24]. Individual constituents of Fructus Schisandrae, schisandrin A, schisandrin, and gomisin N were reported to display anti-inflammatory effects [25][26][27]. Therefore, anti-inflammatory activity from CKD-497 could be expected, and in the current study, the production of NO and inflammatory cytokines (IL-8, IL-12, IL-13, TNF-α, and TGF-β1) was suppressed in LPS-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…As Araki et al reported, gomisin N ameliorated LPS-induced inflammation in mice and BV2 cells. The research demonstrated that an elevation of the inflammatory markers induced by LPS was inhibited by gomisin N treatment [ 52 ].…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%